Regulation of mitochondrial bioenergetic function by hydrogen sulfide. Part II. Pathophysiological and therapeutic aspects. (April 2014) - Módis, Katalin; Bos, Eelke M; Calzia, Enrico; van, Harry; Coletta, Ciro; Papapetropoulos, Andreas; Hellmich, Mark R; Radermacher, Peter; Bouillaud, Frédéric; Szabo, Csaba
<x xml:space="preserve">Abstract</x> Emerging work demonstrates the dual regulation of mitochondrial function by hydrogen sulfide (H2S), including, at lower concentrations, a stimulatory effect as an electron donor, and, at higher concentrations, an inhibitory effect on cytochrome C oxidase. In the current article, we overview the pathophysiological and therapeutic aspects of these processes. During cellular hypoxia/acidosis, the inhibitory effect of H2S on complex IV is enhanced, which may shift the balance of H2S from protective to deleterious. Several pathophysiological conditions are associated with an overproduction of H2S (e.g. sepsis), while in other disease states H2S levels and H2S bioavailability are reduced and its therapeutic replacement is warranted (e.g. diabetic vascular complications). Moreover, recent studies demonstrate that colorectal cancer cells up‐regulate the H2S‐producing enzyme cystathionine β‐synthase (CBS), and utilize its product, H2S, as a metabolic fuel and tumour‐cell survival factor; pharmacological CBS inhibition or genetic CBS silencing suppresses cancer cell bioenergetics and suppresses cell proliferation and cell chemotaxis. In the last chapter of the current article, we overview the field of H2S‐induced therapeutic 'suspended animation', a concept in which a temporary pharmacological reduction in cell metabolism is achieved, producing a decreased oxygen demand for the experimental therapy of critical illness and/or organ transplantation. Linked Articles This article is part of a themed issue on Mitochondrial Pharmacology: Energy, Injury & Beyond. To view the other articles in this issue visit http://dx.doi.org/10.1111/bph.2014.171.issue‐8